Frequency of acute myeloid leukemia in children attended in Belém, Pará from August 2005 to May 2009 - Lacy C. B. Junior; Ian E. Levy; Larissa Tatiana V. M. Frances; Alayde V. Wanderley; Rita de Cássia M. Carneiro; Alessandra Q. Bentes (Sociedade Brasileira de Patologia Clínica, 2015)
Introduction: Acute myeloid leukemia (AML) has variable incidence in different regions of Brazil. Objective: To determine the frequency of AML subtypes in children aged 0-17 years attended at Belém, Pará, from August 2005 to May 2009. Patients and methods: A retrospective study was performed with 278 patients diagnosed with acute or chronic leukemia based on clinical and morphological criteria (French-American-British [FAB]/World Health Organization classification [WHO]) and immunophenotyping profile by flow cytometry, to determine the frequency of the subtypes in AML. Results: We found 70 (25.18%) cases of AML, 37 of these (52.9%) were children aged 0-17 years (median age of 7 years and 8 months). There was no statistical difference in relation to gender. We observed a higher frequency of AML subtype M2 (18/37 - 48.6%) and M0/M1 (10/37 - 27%), especially in the first decade of life (16/28 [57.1%] AML M2 and 9/28 [32.1%] AML M0/M1). Conclusion: In the pediatric population, the types of AML M2, M0/M1 and M3 were respectively the most frequent.